Kuantitas dan Kualitas Fodder Jagung, Padi dan Kacang Hijau dengan Waktu Panen yang Berbeda Menggunakan Smart hydroponic Fodder: Quantity and Quality of Corn, Rice and Mung Bean Fodder with Different Harvest Time Using Smart Hydroponic Fodder - Yuni Resti; Ratih Kemala Dewi; Tera Fit Rayani (Departemen Ilmu Nutrisi dan Teknologi Pakan Fakultas Peternakan Institut Pertanian Bogor, 2021)
This experiment was aimed to compare varieties and harvest time of green hydroponic fodder based on it’s quantity and quality. Green fodder is made from corn kernels, mung beans and unhulled rice. Green fodder was grown by mart hydroponics sensors and Arduino systems for controlling the water irrigation system and environmental conditions such as temperature and humidity. Quantity of green hydroponic fodder (corn, mung bean and unhulled rice) based on the biomass production. Quality of green hydroponic fodder based on nutrient content of the forage biomass (dry matter, crude protein, ash, ether extract, crude fiber and nitrogen free extract). Experimental design for fodder productivity was a completely randomized design with 3 x 3 factorial, i.e seed varieties (corn, mung bean and unhulled rice) and harvesting age of the green hydroponic fodder (7, 14 and 21 d). The results showed that total biomass was affected significantly (p<0.05) by harvesting age. Total biomass was increased with longer harvesting age of fodder. Corn green fodder and unhulled rice green fodder produce larger biomass than mung bean green fodder (p<0.05). The nutrient content of greenfodder were higher compared to the seeds. its quality and quantity, the best harvesting age of corn and unhulled rice green fodder was 14 days. Therefore smart hydroponic fodder can be an alternative to provide good quality fodder and land preservative. Key words: feed, hydroponic, green fodder